IMPLEMENTASI LITERASI BUDAYA DAN KEWARGAAN UNTUK MEWUJUDKAN SISWA SD YANG PERCAYA DIRI DAN BERKARAKTER - Aprianti Kartini, Yanti; Azhar, Reynaldi; Fauzi Heka Perdana, Farhan; Rizki Musyafa, Helmi; Septiani Rahayu, Galih (Penerbit Lafadz Jaya, 2026)
This research is motivated by the fact that many schools have not yet systematically integrated cultural and civic literacy into the learning process. This is evident in the lack of programs that combine local culture-based character development and civic values in teaching and learning activities. This study aims to describe and analyze the implementation of cultural and civic literacy in learning at the elementary school level and its impact on the development of student self-confidence and character. Using a qualitative approach, this study involved observations, in-depth interviews, and documentation studies of teachers, students, and educational staff at schools implementing the program. The results indicate that the effective implementation of cultural and civic literacy can strengthen students' cultural identity, increase self-confidence, and instill positive character values. Challenges faced include a lack of resources and teacher training in integrating these concepts comprehensively. These findings emphasize the importance of schools' role as agents of character formation through strengthening cultural and civic literacy so that students can become confident and characterful individuals in social life.